Isolation and identification of lichen photobionts collected from different environments in North of Portugal and evaluation of bioactivities of their extracts - Loureiro, Luís Carlos Sá (2024)
Lichens are organisms constituted by a symbiotic relationship between a fungus (mycobiont) and a photoautotrophic partner (photobiont). Lichens produce several bioactive compounds; however, the biotechnological exploitation of this organism is hampered by its slow growth. To start studying the possibility of exploiting lichens as alternative sources of bioactive compounds, eighteen lichens were collected in the north of Portugal in order to isolate and study the bioactivity of their photobionts. It was possible to isolate and cultivate only eight photobionts. Three of them, LFR1, LFA2 and LCF3, belong to the Coelastrella genus, the other two (LFA1 and LCF1) belong to the Chlorella genus and for the remaining three photobionts, LFS1, LCA1 and LCR1, it was impossible to isolate their microalgae. These only grow in consortium with bacteria and/or cyanobacteria. All extracts showed antioxidant activity, mainly at a concentration of 10 mg.mL1. LFS1, a consortium extract, showed the highest antioxidant power, as well as the highest concentration of phenolic compounds (5.16 ± 0.53 mg of gallic acid equivalents (GAE).g1). The extracts under study did not show significant antibacterial activity against Escherichia coli, Listeria or Salmonella. The Coelastrella sp. and LFA1 extracts showed the highest hyaluronidase inhibition. The LFR1 extract at a concentration of 5 mg.mL1 showed the highest anti-inflammatory activity (79.77 ± 7.66%). The extracts of Coelastrella sp. and LFA1 also showed greater antidiabetic activity, demonstrating the high inhibitory power of -amylase and -glucosidase. LFR1 at a concentration of 5 mg.mL1, due to its selective cytotoxicity inhibiting the growth of cancer cells (Caco-2 cells), is a promising anticancer agent.